Identification of aldolase C, actin related protein 2 homolog, and enolase 1 as potential biomarkers for electrically stunned chickens - Abu Samah, Norshahida; Amid, Azura; Yusof, Faridah (2014)
Halal slaughtered chicken is a major concern amongst Muslims. Currently, stunning methods has been adopted worldwide aiming at maximizing production and fasten up the slaughtering process. However, stunning treatment which is not in compliance with the Islamic teaching will end up with unlawful chickens for Muslim consumption. In this study, proteomics methods have been used to identify potential biomarkers for the effects of electrical stimulation on the protein profiles of chicken’s brain. The protein profiles were constructed in order to detect any differences in the protein expression and modifications. The electrical stimulation was conducted with different current and voltage. The different voltages studied were 10 V, 40 V and 70 V while the values for current studied were 0.25 A, 0.5 A, and 0.75 A. The profiles from these electrically stimulated chicken were compared to the 0 A, 0 V non stunned sample. After the proteomics analyses using 2D Platinum ImageMaster 6.0 and Matrix-assisted laser desorption/ionization with time-of-flight mass spectrometry (MALDI-TOF) identification, Aldolase C, Actin Related Protein 2 Homolog (ARP2) and Enolase 1 were identified to be positively present in the brain sample of electrically stimulated samples. The over expression of the proteins were further confirmed at the transcriptional level by Real Time PCR. Results from MALDI-TOF and Real Time PCR were in agreement. Therefore, this identification of biomarkers for electrically stimulated chicken’s brain provides a novel approach on differentiating the stunned chickens from the non-stunned ones.